Numerical Investigation of Bolted Hybrid Steel-Timber Connections - Tsalkatidis, Themistoklis; Amara, Youcef; Embaye, Samuel; Nathan, Einar (Frontiers in Built Environment, 2018)
Hybrid steel to timber connections are found in many buildings and bridges. These connections offer several advantages such as ease of construction and energy dissipation. This research paper aims to study the mechanical behaviour of bolted hybrid connections that consists of a square hollow steel column (SHS) and a glulam timber beam. The connection between the two structural members is achieved by means of angles and preloaded bolts. A reference model is constructed and verified by comparison to experimental and numerical data from the international literature. Additionally, several parameters that affect the response of the connection are modified in order to investigate and quantify their effect, resulting in seven different case studies. These parameters are the size of the bolts, the thickness of the angles and the addition of stiffener. The moment- rotation curve of each case study is constructed and the results are commented. Finally, a proposed optimal configuration of the hybrid connection is presented.